¿CIUDADANAS? MUJERES INDÍGENAS EN COSTA RICA: PROBLEMÁTICA HISTÓRICA E HISTORIOGRÁFICA SOBRE SU ACCESO A LA CIUDADANÍA. - Robles Santana, Mª Aránzazu (2012)
The new Costa Rican society that emerges as a result of the independence, gives a new dimension to women´s rol. Women, although with obstacles, will achieve the social and political space that had been denied to them. In this sense, they will be redefining their new identity as well as, the new gender relations which transcend from it. In this process in which a priori, indigenous women are excluded, it is essential to make them visible, within this kind of historical researches.